Data Envelopment Analysis (DEA): New Approach to Measure Financial Efficiency of Banks - Sneha R (The journal of contemporary issues in business and government, 2020)
Data Envelopment Analysis (DEA) is a popular non-parametric test approachused to measure the production frontiers of financial institutions such as Banks. DEAmeasuresthe optimal combinationofinputs thathelp firms realisehigherreturns.Understanding the relative efficiency and performance of banks compared tothe market over a period of time is extremely important for analysts, practitioners, andpolicymakersalike. Inthepresentcase,DEA isemployedtomeasurethefinancialefficiencyofthebanks, referred to as Decision Making Units (DMUs), and to understand how theseDMUsemploytheirinputstogainoptimaloutputs.Thebankperformanceisquantifiedinter msoftheirproductivityorefficiencywhichisgivenbytheratioofthetotaloutputsto total inputs.